2009
DOI: 10.1111/j.1532-849x.2009.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Stress Analysis of Diastema Closure with Ceramic Laminate Veneers

Abstract: The extensions of PLV in diastema closure have more of an esthetic than functional consideration, but critical factors such as angulations and the loading level acting on the free extension of PLV are important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
(71 reference statements)
3
7
1
1
Order By: Relevance
“…This result is in agreement with that of other authors. [12,13,14] On the other hand, the results of this study are incompatible with that of other studies, [30,31] in which the traditional inter proximal preparation design without involvement of contact area exhibited better fracture resistance than in proximal preparation with contact involvement attributing their results by that, the stress levels increase on the incisal edge with an increase in extension of the interproximal preparation (it should be noted that, they used porcelain material rather than IPS e max press that has been used in this study).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is in agreement with that of other authors. [12,13,14] On the other hand, the results of this study are incompatible with that of other studies, [30,31] in which the traditional inter proximal preparation design without involvement of contact area exhibited better fracture resistance than in proximal preparation with contact involvement attributing their results by that, the stress levels increase on the incisal edge with an increase in extension of the interproximal preparation (it should be noted that, they used porcelain material rather than IPS e max press that has been used in this study).…”
Section: Discussioncontrasting
confidence: 99%
“…The basic geometric configurations of the different laminate veneer designs and its dimensions in millimeters in addition to 30 µ thickness of bonding agent layer with 100 µ thickness of resin cement layer were introduced into the ANSYS software program to obtain the nine models "as seen in Table 1". Young's Modulus, and Poisson's ratio of the tooth components as well as the used materials" as seen in Table 2", [17,18,19] were introduced to the ANSYS software program which in turn calculated stresses under a load of 100 N at 60° (tearing) and 125°(protrusion) [20] to identify maximum Von Mises equivalent stresses (in X, Y, Z directions) =…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the load cases, when conducting a FEA study, the simulated occlusal forces with oblique angles should be considered rather than the forces with vertical angles. Previous studies demonstrated that oblique loading forces generated more stress when compared to vertical loading forces . The results of this study confirmed the significant effect of eccentric lateral force angles to generate high tensile stress in the FDPs.…”
Section: Discussionsupporting
confidence: 87%
“…However, Hojjatie and Anusavice analyzed the influence of the pulp chamber and found that the absence or presence of this region within the FEM had a negligible influence on the stress distribution and magnitude in their tested glass‐ceramic crowns and dentin . Chander and Padmanabhan stated that stress distribution is not affected significantly by the simulation of a pulp chamber . Both studies accounted for the negligibly small Young's modulus of the pulp chamber.…”
Section: Discussionmentioning
confidence: 99%